Characterization of chemical composition of eco-enzyme derived from banana, orange, and pineapple pineapple peels - A. Y. Ismail; M. F. Nainggolan; S. Aminudin; R. Y. Siahaan; F. Dzulfannazhir; H. N. Sofyan (Brazilian Journal of Biology)
Abstract Fruit peels such as Banana, Orange, and Pineapple can be used to produce eco-enzymes producing diverse chemical compounds. Eco-enzymes are derived from the organic fermentation process of the specified ingredients. The objective of this study was to characterize the organic compounds present in Eco-enzymes derived from various raw materials. The research phase involved the extraction of eco-friendly Eco-enzymes from different raw materials and the identification of the chemical compounds in them. The results of this study are expected to contribute to organic waste management, highlighting the importance of utilizing waste as an economically and environmentally viable resource and strategic steps in a more sustainable waste management. Data analysis of the Eco-enzyme extraction results was carried out using high-liquid chromatography (HPLC) to ascertain the levels of organic chemical compounds produced. The findings revealed eight organic compounds categorized into organic acids (acetic acid, citric acid, lactic acid, oxalic acid) Acetic acid compound in pineapple fermentation 1.83 (g/L). Citric acid compound in banana peel fermentation 3.39 (g/L). Lactic acid compounds in orange fermentation 4.89 (g/L). The highest oxalic acid compound was identified in orange fermentation with a content of 0.1764 (g/L).